Risk Assessment For Type 2 Diabetes Using The Finnish Diabetes Risk Core Instrument - Budiawan, Heri; Solihatin, Yuyun; Brahmantia, Bayu; Permana, Azril Rizqi; Pangripta, Genta; Abdurrahman, Imam (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Indonesia ranks sixth in the world in the number of people with diabetes with an increase in prevalence from 5.7% in 2007 to 8.5% in 2018. This study aims to describe the risk factors for T2DM in the community who visit the Tamansari Health Center, Tasikmalaya City. This study is a descriptive quantitative study with a cross-sectional design. Respondents as many as 100 people were selected using the total accidental sampling method. Data were collected using the Finnish Diabetes Risk Score (FINDRISC) questionnaire which includes various T2DM risk factors, such as age, gender, body mass index (BMI), waist circumference, physical activity, hypertension, and family history. The majority of respondents were female (68%) with an average age of 45.29 years. A total of 39% of respondents had hypertension, and 39% were physically inactive. The mean BMI of the respondents was 24.83 kg/m², close to the overweight category, while the mean waist circumference was 83.21 cm, indicating abdominal obesity in some respondents. A total of 13% of respondents had a family history of T2DM, and the risk level of T2DM showed that 49% were at low risk, while the other 51% were at risk levels varying from slightly elevated to very high. The main risk factors identified were age, abdominal obesity, hypertension, physical inactivity, and family history. Most of the respondents were at low risk, but 51% were at increased to very high risk. Lifestyle-based interventions such as weight management, increased physical activity, and early detection are needed to reduce the prevalence of T2DM in this population.